NEETs in European rural areas Individual features, support systems and policy measures - Simões, Francisco; Erdogan, Emre (SpringerBriefs in Sociology, 2024)
This open access book constitutes a transnational and multidisciplinary inquiry of the most pressing challenges faced by young people Not in Employment, nor in Education or Training (NEET) in rural areas across Europe. . Rural NEETs are one of the most invisible segments of the youth population, in spite of the fact that the percentage of NEETs is higher in the countryside, compared to those in suburban and urban areas across the EU and many of the Southern and Eastern European countries. This book identifies and analyses different factors that may contribute to or hamper youth social development and social inclusion. Among them are main individual features of rural NEETs, the quality and characteristics of rural NEETs' informal social networks and support, the singularities of formal and non-formal education in rural areas and how they shape the transition from school to work, the role of employment services in providing adequate institutional support, the importance of policy package designor the role of new paradigms of rural development to uphold vulnerable young people in the European countryside . The contributions offered in this book provide a new model of analysis and comprehension of rural NEETs' personal development and social inclusion. This book therefore establishes the state of the art regarding available knowledge on rural NEETs, and represents an inspirational resource for new research agendas on the subject of vulnerable rural youth in Europe. This book also forms the policy design in areas such as education, employment, and social welfare in rural areas.